Cidade dos motoboys: apropriação de espaços na metrópole paulistana - Ito, Roberto Shinji (2010)
This paper focuses on the young motorcycle couriers motoboys - from São Paulo and their relations with the metropolis spaces, the uses of traffic routes and the reserved parking spaces for motorcycles, among other forms of appropriation of the city. As a methodological option, with an emphasis on the field survey and ethnographic work, some data collection instruments were privileged, such as: participating observation, in-depth interviews and the analysis of the audio-visual production from the group that is responsible for Canal Motoboy. From this choice comes a protocol of analysis that is able to answer through the incorporation of the motoboys own narratives some questions related to the conflicts and disputes that are inherent to this way of insertion on everyday life in the city, especially when it comes to conflicts for space in traffic, which is a central element of tensions. From the theoretical and conceptual point of view, the reflection privileges, among others, the concepts of space and metropolis, highlighting the emergence of these new subjects motoboys -, inhabitants of a city that grew disorderly and needs agility in the traffic flow to keep up with the speed of its communication and information; however, it did not respond well in that which concerns the road system. In this mismatch arises, therefore, a hybridization process between the professional motorcyclists and the arcaic road system